Publicystyka polityczna Dmytra Doncowa z lat 1910-1944 w świetle politolingwistyki - Tomanek, Przemysław B. (Księgarnia Akademicka Publishing, 2020)
POLITICAL JOURNALISM OF DMYTRO DONTSOV BETWEEN 1910–1944 FROM THE PERSPECTIVE OF POLITICAL LINGUISTICS The aim of this dissertation is to carry out a linguistic analysis of the texts written and published by the Ukrainian politician, political thinker, and ideologist Dmytro Dontsov (1883–1973). The analysis of the material is made with the use of the tools of political linguistics, including the tools of pragmalinguistics and the theory of speech acts. The task undertaken by the present author is to investigate the language of political journalism of Dontsov from the perspective of political linguistics. The analysis is carried out within this scientific subdiscipline, benefiting from the latest achievements in the field of linguistics. Particular attention is paid to the pragmatic analysis of language, including the theory of speech acts, describing such phenomenon as manipulation, persuasion, eristic and stylistic functions, etc. The analysis covers over one hundred representative texts of the Ukrainian journalist published between 1910–1944. The monograph supplements the research carried out from the historical and political prespectives with a linguistic view, creating an opportunity to see – on a wider landscape – the evolution of the Ukrainian political thought of the first half of the twentieth century, both in its form and content.